Akomodasi Linguistik Antaretnis pada Pedagang di Pasar Kodok Tabanan - I Dewa Ketut Oka Suka Atmaja; Ni Made Dhanawaty (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2020)
This research was related to interethnic linguistic accommodation for traders in the Pasar Kodok Tabanan. The heterogeneous demographics of traders in the Pasar Kodok Tabanan triggered accommodation. This study discussed two main problems that becoming the research study, namely: (1) interethnic accommodation models in the Tabanan Kodok Market, (2) factors causing interethnic accommodation in the Tabanan Kodok Market. The approach model used in this study was a mixed method. The theory used to analyze the problems in this study was sociolinguistic theory including language accommodation which was used as a grand theory and it was supported by other sociolinguistic theories. The results of the analysis showed that, of the 60 respondents the traders in the Tabanan Kodok Market indicated that traders in the Pasar Kodok Tabanan were classified as heterogeneous and were a bilingual or even multilingual community. The accommodation model found in traders in the Pasar Kodok Tabanan based on their accommodation direction, namely EJ and EM, tends to have horizontal convergence, while EB tends to convergence upwards.